A fiber optic methane sensor based on wavelength adaptive vertical cavity surface emitting laser without thermoelectric cooler. (February 2016) - Li, Yanfang; Chang, Lin; Zhao, Yuejin; Meng, Xiangjun; Wei, Yubin; Wang, Xiaosong; Yue, Jianhui; Liu, Tongyu
Abstract: Based on Tunable Diode Laser Absorption Spectroscopy (TDLAS) technique and the feature of Vertical Cavity Surface Emitting Laser (VCSEL) wavelength scanning range up to dozens of nanometer, methane detection technique based on wavelength adaptive VCSEL without Thermoelectric Cooler (TEC), is proposed, then the laser methane sensor system design is followed. The reliability experiments study under variety of environments in laboratory, such as temperature impact test, damp heat, and cyclic and dusty impact test, were carried out. And then the test data and some analysis were given. These data verified the feasibility of the wavelength adaptive technique, and these data showed the laser methane sensor can provide long working time without any calibration, and they have the advantages of high accuracy and stability.